It is union and liberty : Alabama coal miners and the UMW - Brown, Edwin L.; Davis, Colin J. (Colin John), 1954- (University of Alabama Press, 1999)
Much of Alabama's labor history is written in its coalfields. This book records the critical contribution that District 20 of the United Mine Workers of America played in the state's labor movement through its strong stands on such issues as child labor, public education, and interracial unions.